Influence of Thermal Processing on In Vitro Starch Digestibility in Cereal-Based Infant Foods - Marianela D. Rodríguez; Nicolás F. Bongianino; Alberto E. León; Mariela C. Bustos (Foods)
Early-life nutrition is crucial for healthy infant development. This study explored the effects of high-temperature (30 min, 121 °C) and high-humidity treatments on the starch properties and digestibility of infant purees made from wheat, rice, and maize. Purees were prepared using whole grains (WGs), whole grain flours (WGFs), and flour suspensions (FSs) subjected to thermal treatment. Untreated whole grain samples from each cereal served as controls. Samples were analyzed for microstructure, thermal properties, viscosity, and starch digestibility. Microstructural analysis revealed partial to complete loss of amyloplast birefringence, particularly in FS. The thermal treatment reduced peak viscosity in WGs, WGFs, and FSs. Also, the flour suspensions showed lower thermal stability and a phytic acid content reduction of 30%. In vitro digestion revealed a significant reduction in total hydrolyzed starch (THS) in wheat- (27.8 g/100 g starch) and maize- (11.3 g/100 g starch) WG purees compared to controls. In contrast, WGF purees showed significant increases in THS: 29% (wheat), 70% (rice), and 92% (maize). FS purees also showed significant increases in THS (57.4, 39.3, and 45.4 g/100 g starch for wheat, rice, and maize, respectively), alongside a decrease in resistant starch. In conclusion, thermal treatment modulates starch digestibility and viscosity properties in a cereal-dependent manner, offering a potential approach to optimize infant nutrition.